IMPLEMENTASI KURIKULUM DEEP LEARNING DI MADRASAH IBTIDAIYAH: PELUANG, TANTANGAN, dan STRATEGI di MI RIYADLUS SHOLIHIN - Zakia Rohalia; Setiowati Ningsih, Ika Rohmah; Kholilur Rohman Arif; Misnari; Muhammad Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Global educational developments have encouraged the adoption of deep learning, which emphasizes deep understanding, critical thinking, and meaningful learning experiences. In the context of Islamic primary education, the implementation of deep learning presents unique characteristics as it must be integrated with Islamic values. This study aims to explore teachers’ understanding, opportunities, challenges, and strategies in implementing a deep learning-based curriculum at MI Riyadlus Sholihin. This research employed a qualitative approach using a case study design. The participants consisted of classroom teachers, subject teachers, and the principal, selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and analyzed thematically. The findings indicate that teachers’ understanding of deep learning varies considerably. Opportunities for implementation are supported by the alignment with madrasah values, close teacher–student relationships, and a collaborative school culture. However, teachers face challenges related to limited pedagogical understanding, time constraints, and administrative workload. Teachers adopt adaptive strategies by contextualizing learning with students’ daily lives and Islamic values, supported by the instructional leadership of the principal.